Measuring time delays – II. Using observations of the unresolved flux and astrometry. Issue 3 (27th August 2021) - Springer, Ofer M; Ofek, Eran O
ABSTRACT: Lensed quasars and supernovae can be used to study galaxies' gravitational potential and measure cosmological parameters. The typical image separation of objects lensed by galaxies is of the order of 0.5 arcsec. Finding the ones with small separations, and measuring their time delays using ground-based observations is challenging. We suggest a new method to identify lensed quasars and simultaneously measure their time delays, using seeing-limited synoptic observations in which the lensed quasar images and the lensing galaxy are unresolved. We show that using the light curve of the combined flux, and the astrometric measurements of the centre-of-light position of the lensed images, the lensed nature of a quasar can be identified, and its time delay can be measured. We provide the analytic formalism to do so, taking into account the measurement errors and the fact that the power spectra of quasar light curves is red. We demonstrate our method on simulated data, while its implementation to real data will be presented in future papers. Our simulations suggest that, under reasonable assumptions, the new method has the potential to detect unresolved lensed quasars and measure their time delays, even when the image separation is about 0.2 arcsec, or the flux ratio between the faintest and brightest images is as low as 0.05. python and matlab implementations are provided. In a companion paper, we present a method for measuring the time delay using the combined flux observations. This method may be useful in cases in which the astrometric information is not relevant (e.g. reverberation mapping).